Self-esteem and locus of control as mediators between parent-child attachment and attitude towards sexual behavior among adolescents pregnant out of wedlock - Shahruddin, Nor Jumawaton; Mansor, Mariani; Madon, Zainal; Hamsan, Hanina Halimatusaadiah (Asian Online Journals, 2017)
This study aims to identify the role of self-esteem and locus of self-control as mediators between parent-child attachment and attitude towards sexual behaviours among pre-marital pregnant adolescents. This study utilises the four questionnaires of the Inventory of Parent and Peer Attachment (Armsden & Greenberg 1987), the Rosenberg Self-Esteem Scale (Rosenberg, 1965), Rotter’s Locus of Control Scale (Rotter, 1966), and the Brief Sexual Attitudes Scale (Hendrick & Reich, 2006). Furthermore, the researchers also utilise a sampling technique aimed at pre-marital pregnant adolescents. This study applies the Structural Equation Model (SEM) approach to process mediation analysis using the Smart PLS 8.0 software. The sample size taken for this study is around 145 pregnant teenagers aged between 13 and 25 years. The findings contribute to the evidence of existence of partial mediation between parent-child attachment and attitude towards sexual behaviour as explained through the self-esteem and locus of control mediators. The researchers have forwarded a number of suggestions to government and non-governmental agencies to form a strategic treatment plan to help pre-marital pregnant adolescents on the road to recovery, especially in the context of risky sexual behaviour.